Multimodal Representation of Academic Anxiety in Jory John's The Smart Cookie - Anggun Dhanisa; Nabila Zuki; Sarah Safika Sitorus; Ibnati Faiza Hamdi; Muhammad Yusuf (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
Modern children's literature no longer serves merely as a tool for early literacy, but functions as a socio-cultural artifact reflecting the emotional and psychological challenges of contemporary children. However, previous research on how children's academic anxiety and identity crises that are deeply depicted through the synergy of text and imagery in popular storybooks remains highly under-explored. This study aims to examine the multimodal construction in the picture book The Smart Cookie by Jory John and Pete Oswald (2021), specifically how the protagonist's “baked identity” serves as a layered semiotic metaphor for perfectionist pressures and academic performance anxiety. Methodologically, this study adopts a qualitative descriptive approach within the Multimodal Discourse Analysis (MDA) paradigm, integrating Michael Halliday's Systemic Functional Linguistics (SFL), Kress and van Leeuwen's visual social semiotics, and intermodal relations. The analysis focuses on the verbal, visual, spatial, and gestural dimensions of 18 selected double-page spreads. The findings demonstrate that the text-image dynamics actively construct a “third story,” a psychological realm arising from the ironic tension and counterpoint between verbiage and illustration. This study concludes that micro-level narrative and visual decisions successfully encode macro-level social anxieties, allowing the storybook to critique academic performativity while simultaneously fostering internal psychological resilience and social-emotional literacy in young readers.